Single Phase Variable Reluctance Motor Design Using Particle Swarm Optimization (Latin-American Journal of Computing, 2024)
Electrical engines are built under electromagnetism concepts to create mechanical power, those can be seen as simple machines, as it depends on reluctance, even being called as “reluctance motor”, what gives this engine the possibility of being widely used for many purposes. The main objective of this research is to minimize copper losses of a single-phase 6x6 variable reluctance synchronous motor. For that, a Particle Swarm Optimization (PSO) algorithm will be used to obtain the optimum configuration through the Finite Elements Method (FEM). In this context, electric motor design equations were dimensioned based on similar machines. The next procedure was to use FEMM (Finite Element Method Magnetics) software, that allows the magnetic flow density analysis inside the motor air gap. Finally, it is noteworthy that the copper losses results were analyzed before and after the variable reluctance motor optimization with computational tools.